DRG payment does not predispose to negative clinical outcomes in general surgery cases: evidence from a tertiary hospital in China - Hou, Rui; Liu, Xiaokun; Chen, Weijie; Tan, Xutong; Li, Zhe; Zhu, Weiguo; Wang, Weibin (Frontiers in Public Health, 2025)
BackgroundDiagnosis-related group (DRG) payment has proven effective in improving efficiency and containing medical costs. However, concerns persist regarding its potential negative impact on healthcare quality. This study aimed to investigate the association of DRG payment with negative clinical outcomes in general surgery cases.MethodsThe study utilized clinical and insurance data from patients undergoing elective general surgeries at authors' institution between March 2019 and February 2025, with the DRG payment officially implemented in March 2022. Changes in average costs and length of stay (LOS) before and after the DRG payment were assessed using t-tests. To evaluate the reform's impact on healthcare quality, interrupted time series analysis (ITSA) was applied to examine changes in the rates of five negative clinical outcomes: in-hospital mortality, unplanned readmission within 31 days, red blood cell transfusion exceeding 10 units, LOS exceeding 30 days, and unplanned reoperations.ResultsThe sample included 38,014 discharged cases, including 18,666 cases before and 19,348 cases after DRG implementation. Five groups with the highest case volumes were KD1 (thyroid surgery), GB2 (major operation of intestines and colorectum), HC2 (cholecystectomy), GB1 (major operation of stomach and duodenum), HB1 (major operation of pancreas and liver). Following DRG payment, significant reduction in costs was observed in GB2 and GB1, while significant reduction in LOS was observed in groups GB2, HC2 and HB1. ITSA revealed no significant changes in level or trend for any of the five negative clinical outcomes, either in the overall sample or in the subgroups.ConclusionFor patients undergoing general surgeries, DRG payment promoted efficiency without increasing the risk of negative clinical outcomes.